2014
DOI: 10.1371/journal.pone.0096187
|View full text |Cite|
|
Sign up to set email alerts
|

Simplification to Abacavir/Lamivudine + Atazanavir Maintains Viral Suppression and Improves Bone and Renal Biomarkers in ASSURE, a Randomized, Open Label, Non-Inferiority Trial

Abstract: ObjectiveSimplification of antiretroviral therapy in patients with suppressed viremia may minimize long-term adverse effects. The study’s primary objective was to determine whether abacavir/lamivudine + atazanavir (ABC/3TC+ATV) was virologically non-inferior to tenofovir/emtricitabine + atazanavir/ritonavir (TDF/FTC+ATV/r) over 24 weeks in a population of virologically suppressed, HIV-1 infected patients.DesignThis open-label, multicenter, non-inferiority study enrolled antiretroviral experienced, HIV-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…A randomized multicentre study [14] has shown that this switch maintained A greater increase in total cholesterol, HDL and LDL was also observed in switch arm without differences in other lipid parameters. Renal function showed a significant improvement in switch arm.…”
Section: Toxicity Issuesmentioning
confidence: 94%
See 2 more Smart Citations
“…A randomized multicentre study [14] has shown that this switch maintained A greater increase in total cholesterol, HDL and LDL was also observed in switch arm without differences in other lipid parameters. Renal function showed a significant improvement in switch arm.…”
Section: Toxicity Issuesmentioning
confidence: 94%
“…Another option to simplify the regime in patients on a PI is to switch from tenofovir/emtricitabine (TDF/FTC) + ATV/r to ABC/3TC + ATV [14]. However, it should be noticed that, because of ATV-TDF interaction, the combination of TDF/FTC plus unboosted ATV is not a viable option [15].…”
Section: Simplification Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, switching to simplify to a triple nucleoside regimen is not recommended . For PIs, recent studies have evaluated both within‐class switching and simplification to an unboosted regimen . These changes have been to reduce bilirubin, lipids or bone and renal biomarkers.…”
Section: Supporting Individuals On Therapymentioning
confidence: 99%
“…A number of studies also suggest that treatment with tenofovir-DF/ emtricitabine with atazanavir-r decreases inflammatory and hypercoagulation markers [17][18][19] but tenofovir-DF has been associated with renal impairment especially when combined with PIs such as atazanavir-r [20][21][22][23]. On the other hand, conflicting results occur concerning the effect of abacavir/lamivudine/atazanavir-r regimen on markers of systemic and/or chronic inflammation [17,18,24,25].…”
mentioning
confidence: 99%